FDI determinants in Europe and Chinese influence - Dorakh, Alena Rygorayna (Serbian Journal of Management, 2021)
Despite recent concerns about the increasing influence of outside investors on the European Union (EU) and Western Balkans, the developed European countries are still a dominant source of foreign direct investment (FDI) in the region, confirming the benefits of EU membership. At the same time, fast-growing connectivity and lower trade costs in accession and neighboring countries determine the FDI growth from China, particularly via the Belt and Road Initiative (BRI). By applying panel data over 2000-2019 for 34 countries, which form 89% of all European FDI, we first examine FDI patterns around Europe, compare the EU, NMS, and Western Balkans; verify the importance of EU membership for FDI, caused reducing trade costs and improving connectivity. Thus, the new EU member states (NMS) and Western Balkans appear both as a home country and as a pre- entry destination to the EU. Then, we calculate trade costs indices for each selected country and partners over time and find that Europe and China are closely interconnected through trade and FDI. It means that stronger ties with China can be realized for the sample countries at the cost of easing relations with the EU. Finally, incorporating trade costs indices into the FDI model; we evaluate the impact of connectivity on FDI and estimate how BRI affected FDI in Europe. Additionally, we validate that the old framework of horizontal and vertical FDI not representative well and even new complex vertical or export-oriented FDI strategies are shifting today.